Public and private sector cooperation for improved housing delivery systems in rural areas - a case study of Ahanta West District - Kpakpo Pappoe, Frederick Reginald (2012)
A thesis submitted to the department of planning, faculty of environmental and development studies university of science and technology, kumasi, in partial fulfilment of the requirements for the award of a Master of Science in Development Planning and Management.